How founders establish legitimacy A narrative perspective on social entrepreneurs in a developing country context - (:unkn) unknown (EMERALD GROUP PUBLISHING LTD, 2020)
Purpose The purpose of this study is to identify the ways in which social entrepreneurs use rhetoric to establish legitimacy for themselves and their ventures. This is done by examining interviews with 19 social entrepreneurs in the city of Istanbul, Turkey. Most entrepreneurship studies are rooted in a positivist paradigm, but as there is need for qualitative research in entrepreneurship that allows for an in-depth study of a given phenomenon, the life story method is used as a methodological tool as scholars in rhetoric, technical and professional communication have pointed to narratives as viable sites of study. Design/methodology/approach This study used a linguistic focus on entrepreneurship research, thereby contributing to a growing body of literature and responding to Lounsbury and Glynn's call for a more ethnographic approach to entrepreneurial stories to better understand how entrepreneurs use stories as a mechanism for resource and legitimacy acquisition. Findings This paper sought to identify the ways in which social entrepreneurs establish legitimacy for their ventures among various stakeholders, including investors as well as employees, customers and community members. This study aimed to investigate this particular field because, although there has been a recent growth in social entrepreneurial activity in the context of developing nations, the field is still emerging as an area for academic inquiry. Based on interviews with 19 social entrepreneurs in the city of Istanbul, Turkey, four key rhetorical strategies used to establish the legitimacy of social ventures among various stakeholders are identified. Originality/value This study addresses issues related to entrepreneurship from a rhetorical perspective and helps explain the mechanisms through which entrepreneurial phenomena occur. By integrating a rhetorical analysis with reflexive accounts from entrepreneurs, this work directly engages with Downing's (2005) call to use such an approach to develop an enriched account of the duality of structure and agency in entrepreneurial endeavors. In doing so, it also responds to the call to challenge elite functionalist discourses in entrepreneurship research and put forward a view on entrepreneurial performance that acknowledges the socially dependent and constructed nature of such activity. This research has implications for practice as well. New venture founders who enter into conversations with stakeholders can use this typology to assess and improve the language they use to claim legitimate distinctiveness. The typology may, for example, help entrepreneurs who are preparing a business plan or a pitch for investors.
Keywords: Social entrepreneurs; Legitimacy; Developing economy; ORGANIZATIONS; DISCOURSE; FAILURE; STORIES; NEED